Toluene abuse as a contributing factor in a case of fatal autoerotic asphyxia - Handlos, Petr; Gebauerová, Vladimíra; Papoušek, Roman; Handlosová, Klára; Dokoupil, Marek; Klabal, Ondřej; Uvíra, Matěj (Legal medicine (Tokyo, Japan), 2022)
Autoerotic asphyxia is a form of deviant sexual behavior that seeks sexual gratification by means of manipulation with one's own body resulting in asphyxia, and may sometimes turn out to be fatal. Autoerotic fatalities involving autoerotic asphyxia are divided into two groups: "typical" autoerotic fatalities involve mechanical compression of the neck, chest or abdomen, whereas "atypical" autoeroticism involves sexual self-stimulation by other means. Cases where asphyxiophilic behavior is accompanied by volatile substance abuse are reported to be rather rare, but may involve a high risk of fatal results. This paper presents a case of accidental "atypical" autoeroticism involving victim's abuse of toluene, which, combined with asphyxiophilic airway occlusion, led to death. For the sake of comprehensiveness, both a verbal description and a schematic representation of the major metabolic pathways of acute and chronic abuse metabolic markers is provided.
Keywords: Intoxication; parafilie; Asphyxia; lidé; Accidents; úrazy a nehody; Sexual Behavior; sexuální chování; Paraphilic Disorders; Autoerotic death; toluen; Death scene investigation; Substance-Related Disorders; Volatile substances; Toluene; poruchy spojené s užíváním psychoaktivních látek; Autoerotic asphyxia; asfyxie; Humans